2022
DOI: 10.1039/d2tb00300g
|View full text |Cite
|
Sign up to set email alerts
|

Oral nanozyme-engineered probiotics for the treatment of ulcerative colitis

Abstract: Background: Probiotic-based therapy for ulcerative colitis (UC) is a novel and promising approach that has gained much popularity in recent years. However, probiotics may be easily captured and destroyed by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…Here, we found that both postbiotics and probiotics administration protected against DSS-induced colitis, reflected by the decreased histology scores in Postbiotic and Probiotic groups compared with DSS group. However, neither the postbiotic nor probiotic application significantly affected weight loss, DAI, and colon length in mice with colitis, which were inconsistent with previous findings showing protective effects in these aspects [39][40][41] . The discrepant results between this and previous studies in the protective effect against DSS-induced colitis could be due to the different strains of postbiotics and probiotics used and different experimental design between studies.…”
Section: Discussioncontrasting
confidence: 96%
“…Here, we found that both postbiotics and probiotics administration protected against DSS-induced colitis, reflected by the decreased histology scores in Postbiotic and Probiotic groups compared with DSS group. However, neither the postbiotic nor probiotic application significantly affected weight loss, DAI, and colon length in mice with colitis, which were inconsistent with previous findings showing protective effects in these aspects [39][40][41] . The discrepant results between this and previous studies in the protective effect against DSS-induced colitis could be due to the different strains of postbiotics and probiotics used and different experimental design between studies.…”
Section: Discussioncontrasting
confidence: 96%
“…However, probiotics are easily caught or destroyed in advance, and only a few probiotics can reach the inflammatory bowel segment. Zhao et al used a Pt nanozyme-liposome coating to wrap a single probiotic, and the nanozyme coating effectively protected probiotics from strong digestive acids and enzymes. Oral administration of probiotics protected by a nanozyme coating can effectively treat ulcerative colitis in mice.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
“…The etiology and pathogenesis of infectious bowel disease (IBD) remain unclear and it is considered to be caused by the interaction of multiple factors, including environmental, genetic, infectious, and immune factors . A large number of studies have pointed out that nanozymes can be used to improve the inflammatory microenvironment in the intestinal tract and remove excess ROS to play a therapeutic role. ,,,, Zeng et al modified CeO 2 NPs with PEG, and the prepared PEG-CeO 2 NPs exerts a therapeutic effect on the mouse colitis model induced by sodium dextran sulfate (DSS). PEG-CeO 2 NPs can improve the inflammatory microenvironment by continuously scavenging ROS, down-regulating the levels of various proinflammatory cytokines, and inducing macrophage polarization and the Th1–Th17 reaction.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
“…They found that liposomes can protect the phages in the stomach and improve the activity of phages in the intestine. Zhao et al (2022) embedded Escherichia coli Nissle in liposome and found that damage to E. coli can be avoided by acids and enzymes in the GIT, and the colonization rate of E. coli Nissle was also improved, resulting in a better treatment of colonic inflammation and regulation of intestinal epithelial barrier homeostasis than the bare E. coli Nissle. Therefore, the use of liposomes to protect and deliver the probiotics and improve intestinal colonization function of probiotics to treat intestinal diseases has become a new trend.…”
Section: The Fate Of the Core Materials After Releasementioning
confidence: 99%